A questão das garantias em finanças de pequeno porte: experiências internacionais e o microcrédito no Brasil - Farias, Marcelo Eisenhower (2011)
Access to small credit is becoming increasingly difficult to get and one of the most important reasons to this is the absence of guarantees offered to the financial institution by the borrower. Microcredit has arisen as a solution to the hindrance of credit access through the use of the co-signers mechanism, in which a group takes responsibility over paying the obtained funding. In Brazil, the main source of funds of the national program of productive microcredit (PNMPO) comes partly from demand deposits of commercial banks which provide credit operations requiring some kind of collateral to solve the problem of conflicting information. What we see in the microcredit program of the country is that a significant amount of the resources which should be addressed to the microcredit is found idle. Thus, the primal aim of this study is to identify and discuss ways of improving guarantees which could be used in the microcredit program of Brazil. To investigate the proposed theme, a bibliographical research was conducted revising the main concepts of the microfinance theory and the guarantee systems. A research on experiences in microcredit programs was also developed, as well as the types of guarantees used in these places, mainly in Latin America and the Caribbean. This study also includes the experiences of some countries which make use of mutualist guarantee systems, with its origin in Europe. Through this study we have identified that we have few guarantee programs in Brazil, instead of a national system of guarantees, as in other countries, such as Chile, where the guarantee fund FOGAPE provides guarantees to financial institutions upon part of the credit operations made by these institutions, including microcredit operations